2012
DOI: 10.2741/e556
|View full text |Cite
|
Sign up to set email alerts
|

The role of micronutrients in the diet of HIV-1-infected individuals

Abstract: Vitamins, zinc and selenium are important micronutrients that play crucial functions at the cellular and molecular level. Immune response of several different cell types can be modulated by these micronutrients. Deficiency in micronutrients has been extensively reported in HIV-1-infected individuals and further correlated with CD4+ T-cell count, HIV-1 plasma viral load, disease progression and mortality. Supplementation by micronutrients has had controversial effects. Thorough future investigations and trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 162 publications
0
13
0
Order By: Relevance
“…The importance of the gut microbiota for the development of the host’s immune system and the suggested connection between gut microbiota and bone mass in mice led the researchers to investigate the impact of probiotic yogurt on bone mass, especially in the HIV- population [29]. Further studies are required to evaluate the gut microbiota and other micronutrients as a novel therapeutic target for osteoporosis [30]. …”
Section: Discussionmentioning
confidence: 99%
“…The importance of the gut microbiota for the development of the host’s immune system and the suggested connection between gut microbiota and bone mass in mice led the researchers to investigate the impact of probiotic yogurt on bone mass, especially in the HIV- population [29]. Further studies are required to evaluate the gut microbiota and other micronutrients as a novel therapeutic target for osteoporosis [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Zinc, selenium, and glutathione [62] have been studied in intervention trials to determine their effects on immune function. Long-term (18-month) zinc supplementation may reduce the likelihood of opportunistic infection in adults and children and improve CD4 counts in adults.…”
Section: Nutritional Interventionsmentioning
confidence: 99%
“…The imbalance between the production of free radicals and the presence of adequate antioxidants causes oxidative stress which further damage biomolecules and accelerate HIV replication. 25,26 Some authors have demonstrated that deficiencies of nutrients could affect immune function, favours viral expression and replication leading to increased morbidity and mortality. 27 Cytokines are necessary for immune system to function optimally.…”
Section: Role Of Trace Elements On the Immune Systemmentioning
confidence: 99%